(untitled) (Scientific journal of the Fergana State University, 2023)
The role of modern pedagogical technologies in improving the quality of education is important. Pedagogical technology is a systematic method of designing, implementing and evaluating educational processes that guarantees student-centered, democratic and reproducible learning outcomes. Its difference from traditional methods is that it is aimed not at memorizing the knowledge given to students, but at performing specific actions at the end of the educational process. The use of pedagogical technologies in teaching lectures on neutron physics serves to improve the quality of education. To date, the Venn diagram is used in teaching english, teaching teachers, teaching mathematics and physics. However, this method has not been sufficiently studied in teaching lectures on neutron physics. This paper presents the use of graphic organizers - Venn diagrams in teaching subjects of neutron physics.